Lima Inside and Out: City Criticism and Transatlantic Censorship around 1800. Issue 2 (1st December 2022) - Gehbald, Agnes
Abstract : Satire was a flourishing literary genre in colonial contexts with the specific mode of city criticism subverting the official order. At the turn of the century, the idea of a city in the Iberian Atlantic world would comprehend a notion of an ordered locus and society. Critiques of the capital of Lima thus included several stereotypes about urban social chaos criticizing the changing reality of late colonial Peru. This article explores the itinerary of a specific book, Lima por dentro y fuera by the Spaniard Esteban Terralla y Landa, published first in 1797, and which offers a rare opportunity to study contemporary judgement and transatlantic censure history. Tracing the processes of printing, reprinting, and recollection at both sides of the Atlantic – in Lima and Madrid – it tells a story of reception and rejection, and of how Spanish colonial authorities tried to prevent the circulation of censorious literature about the viceregal capital.